Reproduction of Violence in Education Integrative Thematic - Pangestuti, Ratna Dewi (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
Integrative thematic education has contributed to the reproduction of symbolic violence through the habitus of the dominant class. This happens because not all agents have the appropriate capital and habitus. This research aims to identify the capital of parents as a representation of learners and teachers as teaching agents. The method used is qualitative with Pierre Bourdieu's generative structuralism approach. Data collection techniques include observation, interview, and documentation. Bourdieu's theory of reproduction and symbolic violence was used as an analytical tool. The results show that popular class students are less able to adjust the habitus recognized in integrative thematic education, so their practices are considered less appropriate. This is because their parents do not have enough capital accumulation to pass on the right habitus in education. In contrast, petty bourgeois class students who have sufficient capital and habitus are considered more appropriate so they rarely experience symbolic violence. Symbolic violence is also experienced by other popular class agents, such as senior teachers who have less cultural capital than junior teachers. Despite these challenges, integrative thematic education is still practiced because it has become a doxa-an established belief-without considering the cultural diversity of learners in rural areas.